Інновації в розвитку земельного кадастру - Чміль, Артем Сергійович (НУБіП України, 2024)
В статті представлена теза доповіді учасника V Міжнар. наук.-практ. конф. «Формування сталого землекористування: проблеми та перспективи» 19 грудня 2024 р. м. Київ

The topic of "Innovations in the Development of Land Cadastre" explores the latest technological advancements and methodologies aimed at improving the management and efficiency of land registry systems. It examines the integration of digital tools, such as Geographic Information Systems (GIS), blockchain technology, and remote sensing, to enhance accuracy, transparency, and accessibility of land data. The research also addresses the role of innovation in the modernization of land cadastre practices, focusing on automation, data integration, and the simplification of landrelated procedures. Furthermore, it analyzes how these innovations contribute to better land management, legal clarity, and sustainable development, as well as their implications for land administration policy and governance.
Keywords: інновації; земельний кадастр; блокчейн; штучний інтелект (ШІ); innovations; land registry; blockchain; artificial intelligence (AI)